2003
DOI: 10.1046/j.1471-4159.2003.01773.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased synaptosomal dopamine content and brain concentration of paraquat produced by selective dithiocarbamates

Abstract: Exposure to pesticides may be a risk factor for Parkinson's disease based on epidemiologic data in humans, animal models and in vitro studies. Different dithiocarbamate pesticides potentiate the toxicity of both 1-methyl-4-phenyl-1,2,3, 6-tetrahydropyridine and paraquat in mouse models of Parkinsonism by an unknown mechanism. This study examined the effects of commercially used dithiocarbamates on Increased dopamine accumulation in synaptosomes was dose dependent and was related to the carbon backbone of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 61 publications
2
43
0
Order By: Relevance
“…Alternatively, MB may itself indirectly or directly induce a persistent stress on the nigrostriatal dopaminergic neurons, such that they are already compromised and vulnerable when PQ exposure occurs. In vitro evidence suggests that an immediate effect MB is altered toxicokinetics of DA, such that efflux is impeded, thus increasing DA concentration [Barlow et al, 2003]. During development, DA has autocrine and paracrine functions [De Vitry et al, 1991;Levitt et al, 1997], but excess intracellular DA may be oxidized and interfere with mitochondrial function [Berman and Hastings, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, MB may itself indirectly or directly induce a persistent stress on the nigrostriatal dopaminergic neurons, such that they are already compromised and vulnerable when PQ exposure occurs. In vitro evidence suggests that an immediate effect MB is altered toxicokinetics of DA, such that efflux is impeded, thus increasing DA concentration [Barlow et al, 2003]. During development, DA has autocrine and paracrine functions [De Vitry et al, 1991;Levitt et al, 1997], but excess intracellular DA may be oxidized and interfere with mitochondrial function [Berman and Hastings, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…One such combination is that of paraquat and the fungicide maneb. The overlap in geographic usage of these compounds was used as a rationale for animal studies that showed that coexposure caused decreased motor activity, altered striatal dopamine and dopamine metabolites, decreased striatal tyrosine hydroxylase and dopamine transporter (DAT) expression and increased accumulation of dopamine in synaptosomes [18,39,40]. However, the compounds are not used simultaneously [ATSDR -CERCLA Priority List of Hazardous Substances (http://www.atsdr.cdc.gov/cercla)] and, although paraquat does persist in the environment (Figure 4), due to its high affinity for soil it is not biologically available, making such simultaneous exposures unlikely in the human population.…”
Section: Paraquatmentioning
confidence: 99%
“…A combination of paraquat with another pesticide manganese ethylene-bis-dithiocarbamate (Maneb) is an alternative formula for PD rodent model establishment. The combination increases the concentration of paraquat and enhances the toxicity to the dopaminergic neurons [38][39][40]. Maneb is a fungicide and used independently to induce PD via a similar mechanism to paraquat, which targets on the mitochondrial complex III [41].…”
Section: Paraquat Modelmentioning
confidence: 99%